Respiratory outcomes after 12 weeks in patients recovered from COVID-19 managed with non-invasive positive pressure ventilation - Mirza Muhammad Ayub Baig, Muhammad Adnan, Zohaib Ramzan, Muhammad Usman Baig, Faaiz Sultan (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the respiratory outcomes twelve weeks after the management with non-invasive positive pressure ventilation (NIPPV) in patients recovered from severe corona virus disease 2019 (COVID-19). Methodology: The cross-sectional analytical study was conducted in the Department of Pulmonology, Sir Ganga Ram Hospital Lahore between October 2020 and March 2021. Total 124 patients visiting the hospital twelve weeks after recovery from COVID-19 were enrolled using convenience sampling. After excluding patients with a history of previous respiratory symptoms before the development of COVID-19, data from 87 patients who required oxygen >15 L/minute and NIPPV support were subjected to final analysis. Results: The proportion of middle-aged adults was 52.9%, males 64.4% and smokers 49.4%. Twelve weeks after treatment with NIPPV, O2 saturation <97.0% at rest was found in 97.7% patients, PR >100 at rest in 16.1% patients, severe dyspnea in 65.5% patients, O2 dependency >5 L/min in 2.3% patients, severe CXR abnormalities in 20.7% patients and lung fibrosis in 27.6% patients. The distribution of SpO2, PR, and dyspnea status twelve weeks after recovery from severe COVID-19 were not significantly different between NIPPV duration groups (p-value >0.05). However, the number of patients with O2 dependency, severe CXR abnormality, and lung fibrosis were significantly different between NIPPV duration groups (all p-values <0.05). Conclusion: Oxygen desaturation, severe dyspnea and severe CXR abnormalities twelve weeks after the treatment with NIPPV were common among patients recovered from COVID-19. Severe CXR abnormality, lung fibrosis, and O2 dependency were significantly associated with prolonged duration of NIPPV.